(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The thymus is the central, or primary, organ of the lymphoid (immune) system. Its main functions are to ensure the maturation and differentiation of thymocytes, the integration of various populations of thymocytes and macrophages to implement immune responses. The article examines and presents the latest scientific data on the development of the thymus, its structure and cellular composition. Both well-known sources and new literature were used. This article indicates the external structural features of the thymus, internal structure, and cellular composition. In particular, attention is paid to the description of the zones of the thymus, since so far there has been no consensus among morphologists on this issue. Embryonic development is described, as well as morphometric parameters during different periods of prenatal development. This article will be useful when writing scientific and diploma works, books, dissertations related to the issue of thymus development, since the most relevant information on this topic is collected here.